Onnamide A suppresses the severe acute respiratory syndrome-coronavirus 2 infection without inhibiting 3-chymotrypsin-like cysteine protease - Hayashi, Yasuhiro; Higa, Nanami; Yoshida, Tetsuro; Tyas, Trianda Ayuning; Mori-Yasumoto, Kanami; Yasumoto-Hirose, Mina; Tani, Hideki; Tanaka, Junichi; Jomori, Takahiro (Journal of biochemistry (Tokyo), 2024)
Given the continuous emergence of new variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the development of new inhibitors is necessary to enhance clinical efficacy and increase the options for combination therapy for the coronavirus disease 2019. Because marine organisms have been a resource for the discovery of numerous bioactive molecules, we constructed an extract library of marine invertebrates collected from the Okinawa Islands. In this study, the extracts were used to identify antiviral molecules against SARS-CoV-2. Using a cytopathic effect (CPE) assay in VeroE6/TMPRSS2 cells, an extract from the marine sponge Theonella swinhoei was found to reduce virus-induced CPE. Eventually, onnamide A was identified as an antiviral compound in the extract using column chromatography and NMR analysis. Onnamide A inhibited several SARS-CoV-2 variant-induced CPEs in VeroE6/TMPRSS2 cells as well as virus production in the supernatant of infected cells. Moreover, this compound blocked the entry of SARS-CoV-2 pseudo-virions. Taken together, these results demonstrate that onnamide A suppresses SARS-CoV-2 infection, which may be partially related to entry inhibition, and is expected to be a candidate lead compound for the development of anti-SARS-CoV-2 drugs.